Chronic bacterial pulmonary infections in advanced cystic fibrosis differently affect the level of sputum neutrophil elastase, IL‐8 and IL‐6. (16th June 2021) - Majka, Grzegorz; Mazurek, Henryk; Strus, Magdalena; Ciszek‐Lenda, Marta; Szatanek, Rafał; Pac, Agnieszka; Golińska, Edyta; Marcinkiewicz, Janusz
Abstract: Advanced cystic fibrosis (CF) lung disease is commonly characterized by a chronic Pseudomonas aeruginosa infection and destructive inflammation caused by neutrophils. However, the lack of convincing evidence from most informative biomarkers of severe lung dysfunction (SLD‐CF) has hampered the formulation of a conclusive, targeted diagnosis of CF. The aim of this study was to determine whether SLD‐CF is related to the high concentration of sputum inflammatory mediators and the presence of biofilm‐forming bacterial strains. Forty‐one patients with advanced CF lung disease were studied. The severity of pulmonary dysfunction was defined by forced expiratory volume in 1 second (FEV1) < 40%. C‐reactive protein (CRP) and NLR (neutrophil–lymphocyte ratio) were examined as representative blood‐based markers of inflammation. Expectorated sputum was collected and analysed for cytokines and neutrophil‐derived defence proteins. Isolated sputum bacteria were identified and their biofilm‐forming capacity was determined. There was no association between FEV1% and total number of sputum bacteria. However, in the high biofilm‐forming group the median FEV1 was < 40%. Importantly, high density of sputum bacteria was associated with increased concentrations of neutrophil elastase and interleukin (IL)‐8 and low concentrations of IL‐6 and IL‐10. The low concentration of sputum IL‐6 is unique for CF and distinct from that observed in other chronic pulmonary inflammatory diseases. These findings strongly suggest that expectorated sputum is an informative source of pulmonary biomarkers representative for advanced CF and may replace more invasive bronchoalveolar lavage analysis to monitor the disease. We recommend to use of the following inflammatory biomarkers: blood CRP, NLR and sputum elastase, IL‐6, IL‐8 and IL‐10. Abstract : Advanced lung cystic fibrosis is associated with P. aeruginosa biofilm infections. Sputum biomarkers are informative to monitor severity of lung inflammation and analysis of expectorated sputum analysis replace usage of more invasive bronchoscopy lavage (BAL). Neutrophil elastase and IL‐8 are key sputum inflammatory markers of lung injury, while low sputum IL‐6 level is a hallmark of lung cystic fibrosis chronic inflammation.